The Influence Of Audit Committee Effectiveness And Financial Condition On Audit Delay In Companies Listed On The Indonesian Stock Exchange - Robby Krisyadi; Bambang Bambang (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The findings based on this study aim to analyze the influence of audit committee characteristics, audit committee diversity, and the financial condition of entities with audit delay. The research sample was created by generating 1019 data using panel data from companies listed on the Indonesia Stock Exchange between 2017 and 2021. Purposive sampling is the technique used in the sample selection process. The findings can be concluded that audit committee size, audit committee independence, audit committee meetings, audit committee accounting skills, female audit committee chairs, age of audit committee members, and corporate news are not necessarily able to have a significant effect on audit delay. However, female audit committee accounting expertise is certainly able to have a significant negative effect on audit delay. The increasing role of women with audit committee expertise will increase the quality of financial reporting, including reducing audit delay. In addition, the age of the audit committee members and financial distress can certainly give a positive significance to audit delay. Thus, the results of this study become an important record for companies and regulators regarding the importance of the role of audit committee diversity and financial conditions on audit delay